„Faciamus experimentum in corpore vili“: From a Critical Analysis of Medical Research Towards an Argumentative Coproduction - Durnová, Anna (Teorie vědy / Theory of Science, 2011)
The book by Grégoire Chamayou, Les corps vils: Expérimenter sur les êtres humains aux 18e et 19e siècles studies practices of medical research in 18th and 19th centuries. Along various stories of „ignoble bodies", as he qualifies human beings that had been subjected to medical research of that time, the author shows that practicing medical research is intrinsically linked to historical and social circumstances. With this thesis, the book responds to the recent critical approaches to medical research that have emphasized that science interacts with society and vice versa. The article summarizes the existing debate in STS, medical sociology and sociology of scientific knowledge in order to present a concept of "argumentative coproduction" which enables to capture the dynamics between science and society, especially the mechanisms that medical research produces to govern societies.